Effects of Organochlorine Pesticide Residues in Maternal Body on Infants - Qi, Shi-Yu; Xu, Xue-Ling; Ma, Wen-Zhi; Deng, Shou-Long; Lian, Zheng-Xing; Yu, Kun (Frontiers in Endocrinology, 2022)
There are many organochlorine pollutants in the environment, which can be directly or indirectly exposed to by mothers, and as estrogen endocrine disruptors can cause damage to the lactation capacity of the mammary gland. In addition, because breast milk contains a lot of nutrients, it is the most important food source for new-born babies. If mothers are exposed to organochlorine pesticides (OCPs), the lipophilic organochlorine contaminants can accumulate in breast milk fat and be passed to the infant through breast milk. Therefore, it is necessary to investigate organochlorine contaminants in human milk to estimate the health risks of these contaminants to breastfed infants. In addition, toxic substances in the mother can also be passed to the fetus through the placenta, which is also something we need to pay attention to. This article introduces several types of OCPs, such as dichlorodiphenyltrichloroethane (DDT), methoxychlor (MXC), hexachlorocyclohexane (HCH), endosulfan, chlordane, heptachlorand and hexachlorobenzene (HCB), mainly expounds their effects on women’s lactation ability and infant health, and provides reference for maternal and infant health. In addition, some measures and methods for the control of organochlorine pollutants are also described here.